Biomarker Responses and Decreasing Contaminant Levels in ringed seal - Kovacs, Kit M.; Krafft, Bjørn; Wolkers, Hans; Helgason, Lisa Bjørnsdatter; Lydersen, Christian; van Bavel, Bert (Norwegian Polar Institute, 2008)
Blubber was analyzed for a wide range of contaminants fromfive subadult and eight adult male ringed seals sampled in 2004,namely, for polychlorinated biphenyls (PCBs), hexachlorobenzene(HCB), toxaphenes, chlordanes, dichlorodiphenyldichloroethylene(DDE), and polybrominated diphenylethers (PBDEs).Contaminant levels were compared to previously sampled animalsfrom the same area, as well as data from literature for otherarctic wildlife species from a wide variety of locations. Ringedseals sampled in 2004 showed 50–90% lower levels of legacy contaminantssuch as PCBs and chlorinated pesticides compared toanimals sampled in 1996 of similar age (14 subadults and 7 adultmales), indicating that the decline of chlorinated contaminantsobserved during the 1990s in a variety of arctic wildlife species iscontinuing into the 21st century. The results also indicated thatPBDE declined in ringed seals; levels in 2004 were about 70–80%lower than in animals sampled in 1998. This is one of the firstobservations of reduced exposure to these compounds and mightbe a first indication that restrictions of production and use ofthese contaminants have resulted in lower exposures in the Arctic.The PCB pattern shifted toward the less chlorinated (i.e., less persistent)PCBs, especially in adult ringed seals, possibly as a resultof reduced overall contaminant exposures and a consequentlylower cytochrome P-450 (CYP) induction, which results in aslower metabolism of less persistent PCBs. The overall effectwould be relative increases in the lower chlorinated PCBs and arelative decreases in the higher chlorinated PCB. Possibly due tolow exposure and consequent low induction levels, ethoxyresorufinO-deethylation (EROD) activity proved to be a poor biomarkerfor contaminant exposure in ringed seals in the present study. Theclose negative correlation (r2=70.9%)between EROD activity andpercent blubber indicates that CYP might respond to increasedbioavailability of the contaminant mixtures when they are mobilizedfrom blubber during periods of reduced food intake.